DEVELOPING STUDENTS SOCIO-CULTURAL COMPETENCE BY USING SOCIO CULTURAL DISCOURSE ANALYSIS METHOD - Kattayeva, Feruza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The process of interpersonal communication is important in the process of growing young people in the educational process to create the necessary conditions for the implementation of their capabilities as a professional, mature specialist. This article draws conclusions of the importance of the English reading of artistic literature in the development of socio - cultural competence of students of higher education institution.